Marketing Innovation of Turmeric Agroindustry Through Information Technology in West Lombok District Regency (Case Study in Gerung District) - Aeko Fria Utama FR; Asasandi, I GN Aryawan (KENDALI: Economics and Social Humanities, 2025)
The purpose of the study was to determine the role of innovation in the marketing of the turmeric agroindustry in Gerung District, West Lombok Regency, namely: (1) to determine the role of innovation in the marketing of the turmeric agroindustry in Gerung District, West Lombok Regency; (2) to determine the benefits obtained when using information technology as a marketing medium; and (3) to determine the obstacles when using information technology in marketing. This study uses a case study method and is located in Gerung District, West Lombok Regency. The determination of respondents in this study was carried out using a purposive sampling technique totaling 20 respondents who are entrepreneurs in the agroindustry of processed turmeric beverages. The results of the study showed (1). Among the several information technologies available, the most important role in the marketing of the turmeric agroindustry is a cellphone with the WhatsApp application, namely with the number of users 20 out of 20 respondents (100%) with an average sales volume of 253 bottles within one week (2). The most benefits felt by respondents in using information technology as a marketing medium for turmeric-based agro-industry in Gerung District are more buyers and orders, with an average of 7 out of 20 respondents (35%) who received these benefits (3). The most common and frequent obstacles experienced by respondents were errors during delivery (delivery time, damaged packaging during delivery, etc.), with 12 out of 20 respondents (60%) experiencing this.